Analisis Pengaruh Motivasi Kerja Terhadap Kinerja Karyawan Roti Ganep - Erwinanto, Erwinanto; , Lukman Hakim S.E, M.Si (2016)
The main goal of research is to know the influence of work motivation on performance of employees. Hypotheses research: Ha: there is an influence employee motivation on performance of employees, Ho: no influence employee motivation employee performance . The population of the research was employees of the company of 140 Ganep bread person but the author only takes as much as 90 respondents because only limited respondent part production. Research data obtained from the dissemination of the questionnaire. Data analysis techniques using test instruments, test the assumptions of classical, linear multiple regression test and test hypotheses. The results showed: 1) individually, responsibility is positive and significant effect on performance of employees, recognition of the positive and significant effect on performance of employees, development of a positive and significant effect on performance, Employee Incentives and significant positive effect on performance of employees, work environment positive and significant effect on performance of employees, a positive and significant effect of security against the performance of the employees, the relationship was not significant and positive effect on performance of employees; 2) collectively the responsibility, recognition, development, incentives, work environment, safety, significant effect relations against the performance of employees. Conclusion the results of the research there were a significant influence on the motivation of working with the performance of the company's employees are bread Ganep. Keywords: Motivation, Employee Performanc